Impact of athletic profiles and the relative age effect on the future achievement levels of young basketball players - Irid, Y.; Pineau, J.-C.; De Larochelambert, Q.; Toussaint, J.-F.; Sedeaud, A. (Frontiers in Sports and Active Living, 2025)
Talent identification in youth sports is a multifactorial process, with athletic profiling and the Relative Age Effect (RAE) playing critical roles. However, few studies have investigated their combined influence on long-term success in youth basketball. This study explores how athletic profiles and RAE influence future success in young male basketball players. A total of 131 players (age: 14.5 ± 0.7 years; height: 180.6 ± 9.7 cm) were assessed on speed, agility, vertical jump, and endurance. RAE was evaluated via birth quarter distribution. A principal component analysis followed by hierarchical clustering revealed four distinct performance profiles: Hybrid (n = 45), Elevated (n = 34), Resilient (n = 35), and Explosive (n = 19). These clusters were cross-referenced with players` future levels of competition: Amateur (n = 105), Developmental (n = 19), and Elite (n = 9). Both athletic profiles and RAE showed statistically noteworthy associations with future achievement (p < 0.10). Notably, players in the Resilient cluster—characterized by lower physical test scores and later birthdates—were more likely to reach the Elite level. These findings highlight the importance of accounting for individual developmental trajectories and relative age in talent identification. They support a more holistic, long-term approach to player evaluation, challenging the assumption that early physical superiority reliably predicts future elite status.